Connexin 43 is overexpressed in human fetal membrane defects after fetoscopic surgery†. (25th September 2016) - Barrett, David W.; David, Anna L.; Thrasivoulou, Christopher; Mata, Alvaro; Becker, David L.; Engels, Alex C.; Deprest, Jan A.; Chowdhury, Tina T.
Abstract: Objective: We examined whether surgically induced membrane defects elevate connexin 43 (Cx43) expression in the wound edge of the amniotic membrane (AM) and drives structural changes in collagen that affects healing after fetoscopic surgery. Method: Cell morphology and collagen microstructure was investigated by scanning electron microscopy and second harmonic generation in fetal membranes taken from women who underwent fetal surgery. Immunofluoresence and real‐time quantitative polymerase chain reaction was used to examine Cx43 expression in control and wound edge AM. Results: Scanning electron microscopy showed dense, helical patterns of collagen fibrils in the wound edge of the fetal membrane. This arrangement changed in the fibroblast layer with evidence of collagen fibrils that were highly polarised along the wound edge but not in control membranes. Cx43 was increased by 112.9% in wound edge AM compared with controls ( p < 0.001), with preferential distribution in the fibroblast layer compared with the epithelial layer ( p < 0.01). In wound edge AM, mesenchymal cells had a flattened morphology, and there was evidence of poor epithelial migration across the defect. Cx43 and COX‐2 expression was significantly increased in wound edge AM compared with controls ( p < 0.001). Conclusion: Overexpression of Cx43 in the AM after fetal surgery induces morphological and structural changes in the collagenous matrix that may interfere with normal healing mechanisms. © 2016 The Authors. Prenatal Diagnosis published by John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? After fetoscopic surgery, the fetal membrane fails to heal spontaneously and the membrane defect is prone to iatrogenic PPROM. What Does ThisStudy Add? We observed abnormal connexin 43 expression in the wound edge with preferential distribution in the mesenchymal cells compared with the epithelial cells. The overexpression of Cx43 may interfere with normal healing of the amniotic membrane after fetoscopic surgery.